Body Performance Analysis in Interactive Art Based on Maurice Merleau-Ponty’s Views - Attarian, Mahdi; Marasy, Mohsen (Journal of History Culture and Art Research, 2018)
Maurice Merleau-Ponty is a famous phenomenologist of the twentieth century. Being influenced by Husserl, Merleau-Ponty paid attention to sensory perception and the body topic by rejecting empirical and rational philosophical theories. Merleau-Ponty’s philosophy is around the subject that perception is a physical phenomenon, not a mental event. New artistic media provide an opportunity for audience engagement and experience, and since the experience is always body dependent, body is considered an integral part of the modern media. The purpose of this research is to understand the interaction of audience regarding interactive art effects, relying on Merleau-Ponty’s views. The main research question: What are the commonalities of Merleau-Ponty’s body performance theory in the process of perceiving artwork and interactive art elements? This research is fundamental in terms of purpose and descriptive-analytic in terms of nature with an adaptive approach and library research is used for information collecting. The research results showed that comparing Merleau-Ponty’s views and the interactive art elements, there are commonalities such as sensory perception, audience acting, globalism (Gestalt), interconnectedness and pre-reflective perception. Based on these common features, the new art media, including interactive art, can be analyzed.